The Joint Effect of ESG Practices and Financial Development on the Financial Performance of Asian Companies - Fouda, Ali Yehia (AUC Knowledge Fountain, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) practices, financial development, and financial performance in the Asian markets. This research uses econometric models to analyze two key aspects of financial performance: Return on Assets (ROA), and Tobin’s Q. The results show that there is a negative relationship between ESG practices and financial success, highlighting the financial burden imposed by sustainability initiatives. Machine learning model (XGBoost) has been used to check the robustness of the regression model. Some Commonalities and other differences have been recognized. Yet, the regression model results have been relied upon. Financial development serves as a moderating factor, easing the negative effects of ESG practices on ROA by allowing access to capital and diminishing financial constraints. This effect doesn’t appear in Tobin’s Q, showing a gap between company actions and what investors think. The results show that financial systems help companies combine sustainability with making profits. The research stresses the importance of actions like educating investors to match corporate ESG efforts with their market value. This study provides important information for policymakers, corporate leaders, and investors. It emphasizes the need for a solid financial system and tailored approaches to tackle the challenges of adopting ESG practices in Asia. This research looks at how ESG practices relate to financial growth. It aims to help with sustainable finance and offers advice on how companies can match their sustainability goals with their financial aims. The results show that companies in Asia can lead the global move towards sustainable and strong business practices.